Antimicrobial Use and Susceptibility of Indicator Escherichia coli in Finnish Integrated Pork Production - Sali, Virpi; Nykäsenoja, Suvi; Heikinheimo, Annamari; Hälli, Outi; Tirkkonen, Taneli; Heinonen, Mari (Frontiers in Microbiology, 2021)
In pigs, antimicrobial use (AMU) practices vary at different production phases between herds and between countries. Antimicrobial resistance (AMR) development is linked to AMU but recognized as a multi-factorial issue, and thus, any information increasing knowledge of AMU and AMR relationships is valuable. We described AMU and screened the carriage of different AMR phenotypes of indicator Escherichia coli in 25 selected Finnish piglet-producing and finishing herds that formed nine birth-to-slaughter production lines. Moreover, we studied associations between AMU and AMR in both herd types and throughout the production line. Treatment records were obtained from the national Sikava register for 1year, and AMU was quantified as mg/PCU (population correction unit) and TIs (treatment incidences). For phenotypic antimicrobial susceptibility testing, ten pen-level pooled feces samples (n=250) in each herd were collected from one room representing the oldest weaned piglets or the oldest finishing pigs. Majority of the medications (96.8%) was administered parenterally, and penicillin was the predominant antimicrobial in every herd. More different antimicrobial substances were used in piglet-producing than in finishing herds (median 5 and 1, respectively, p<0.001). As mg/PCU, sows had the highest AMU and suckling piglets had the highest TIs, whereas finishing pigs were the least treated age group. The proportion of susceptible indicator E. coli isolates of all studied isolates was 59.6%. Resistance was found most commonly against tetracycline, sulfamethoxazole, trimethoprim, and ampicillin, and multi-resistant (MR) isolates (46.5% of all resistant isolates) were resistant to a maximum of four different antimicrobials. Quinolone resistance was rare, and no resistance against 3rd-generation cephalosporins, meropenem, azithromycin, colistin, gentamicin, or tigecycline was detected. The main associations between AMU and AMR were found at antimicrobial group level when use was compared with the presence of AMR phenotypes. The proportion of resistant isolates was not associated with AMU, and herd size was not associated with either AMU or AMR. We suggest that the use of narrow-spectrum beta-lactams as a primary treatment option and lack of wide application of oral group medications potentially favors a good resistance pattern in integrated pork production.